VOLCANIC-HYPABYSSAL ROCK GEOCHEMISTRY OF A SUBDUCTION-RELATED MARGINAL BASIN OPHIOLITE: SOUTHEAST BOHOL OPHIOLITE-CANSIWANG MÉLANGE COMPLEX, CENTRAL PHILIPPINES - Faustino D.V.; Yumul Jr.G.P.; Dimalanta C.B.; De Jesus J.V.; Tamayo Jr.R.A.; Zhou M.-F.; Aitchison J.C. (My University, 2006)
The Early Cretaceous Southeast Bohol OphioliteCansiwang Mélange Complex and the Alicia Schist form the basement of southeastern Bohol Island in central Philippines. New geochemical data show that four discrete groups constitute the volcanic and associated hypabyssal rocks of the ophiolite-mélange complex: boninitic rocks (BON), enriched and normal mid-ocean ridge basalt-like rocks (E-MORB; NMORB) and high-magnesian andesites (HMA). Of these four groups, the BON are the most depleted in REEs and with the most pronounced negative Nb anomalies. Both MORB-like types exhibit subduction-zone influence as reflected in their slight negative Nb anomalies. Characteristically with flat and LREE-depleted patterns, the HMA samples appear to mimic N-MORB patterns but with lower REE concentrations. This geochemical diversity is best explained by a suprasubduction zone environment of formation as is also evident from field geological information. Formation of the Cansiwang Mélange is believed to have been concurrent with the ophiolite's emplacement by subduction-accretion along a forearc margin. This tectonic boundary was later jammed into inactivity with the entry of the Alicia Schist that most likely was an oceanic bathymetric high. The intercalation of both tuffaceous materials and pelagic chert with the pillow basalts are consistent with a marginal basin tectonic setting.
Keywords: FOREARC; GEOCHEMISTRY; OPHIOLITE; PHILIPPINES; SUPRA-SUBDUCTION; Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая